Development of Organizational Culture and Educational Traditions of a University: Experience of School of Adviser Curators (Journal of Educational Sciences, 2020)
The article summarizes 10 years of innovative work experience of the School of Curators and Advisers(SCA) at Al-Farabi Kazakh National University. Educational activity in higher education has its owncharacteristics, differs from the school area of activity. It is more professionally oriented, includes thedevelopment of common competencies – communication, resilience, stress resistance, creativity, etc.The article reflects the development of new approaches to the educational work of the university. Thepurpose of the article is to summarize the practical experience of the School of Advisers and Curators atAl-Farabi Kazakh National University, to identify important areas of development of the academic environmentthrough the experience of conducting trainings on educational work, the development of theorganizational culture of teachers and educational traditions, strategies and technologies in universityeducation. Great importance in higher education is attached to the academic environment, the improvementof organizational culture, and through it the development of the social capital of the university. Themain task of work of SCA is to increase the educational competence of curators. As part of the implementationof this task, as the authors note, thanks to the use of training methods for advanced training, theexchange of teachers’ experience, and the creative atmosphere, the functions of relieving social tensionin the team, elements of social therapy, establishing communication, and thus increasing the intellectualand social capital of teachers and organizations, were additionally performed., According to the survey,in which about 300 curators took part, more than 90% of teachers note the usefulness of the trainings.The SWOT-analysis of innovative experience was made.Key words: educational theory, curator, adviser, social capital, academic environment.